Analisis Determinasi Keputusan Pembelian Balokarta: Peran Mediasi Brand Trust: Indonesia - Utami, Alivia Meyrizka; Aresqi, Sevia Windia (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2026)
This study aims to analyze the effect of content marketing, brand image, and electronic word of mouth (e-WOM) on purchase decisions at Balokarta, with brand trust as a mediating variable. This research employs a quantitative approach using non-probability sampling with the purposive sampling method. Data were collected through the distribution of questionnaires using Google Forms to 115 respondents. The data analysis method used in this study is path analysis with the assistance of Statistical Package for the Social Sciences (SPSS). The results indicate that content marketing, brand image, e-WOM, and brand trust have a positive and significant effect on purchase decisions. In addition, content marketing, brand image, and e-WOM have a positive and significant effect on brand trust. The mediation test results show that brand trust is able to mediate the relationship between content marketing, brand image, and e-WOM on purchase decisions at Balokarta.